Mindfulness and Self-Control in Fatherless Adolescents - Agustin, Ardianti; Purwaningtyas, Fifin Dwi; Rahmadian, Muhammad Reza; Yulianasari, Vidi (Esa Unggul University, 2025)
Adolescence was a transitional phase filled with challenges, where self-control was crucial to prevent negative behaviors. In this context, parental involvement, particularly from fathers, plays a vital role in fostering emotional closeness and effective parenting. However, many adolescents grow up without the presence or optimal role of a father (fatherless), leading to diminished self-control and an increased risk of engaging in negative behaviors. The lack of paternal involvement often leaves adolescents struggling to understand themselves and develop positive character traits. This study aims to evaluate the impact of mindfulness therapy in enhancing self-control among fatherless adolescents. Using an experimental approach with a one-group pretest-posttest design, the study involved 13 adolescents aged 14–17 years residing in Surabaya. The mindfulness therapy intervention was delivered intensively to help participants manage emotions and improve self-awareness. Data were analyzed using the Friedman test to examine differences in pretest, posttest, and follow-up scores. The results revealed a significant improvement in self-control following the intervention (Chi-Square = 25.32; p < 0.05). These findings confirm that mindfulness therapy is an effective intervention for fostering self-control in adolescents, particularly within the fatherless group. This intervention holds potential for broader applications in parenting and educational programs to enhance adolescent psychological well-being.